Sustainable evidence-driven school improvement: routines and data use in Estonian schools - Rääk, Katrin; Eisenschmidt, Eve (Frontiers in Education, 2025)
Educational systems worldwide seek sustainable school improvement by fostering collaborative organizational routines that support teachers' practises and students' learning outcomes. This study examines how five Estonian schools perceive evidence-driven school improvement in a 3-year school-university partnership program. In each school, the principal and teachers collaborated with an external mentor. Supported by university experts, the school improvement teams worked on projects aimed at enhancing student learning in their schools and fostering a collaborative, evidence-driven school culture. Data was collected through focus group interviews with the school teams and analyzed using thematic content analysis. The findings reveal that schools view data as connected to accountability and decision-making, with considerably less emphasis on instructional improvement. School organizational and teacher-related factors, together with data overload, hindered systematic data use. Notably, the school improvement program's effectiveness was most evident in the final year, with the sustainability of improvement largely dependent on collaborative routines.